Peran Pemahaman Hakikat dan Prinsip Pembelajaran dalam Merancang Strategi Mengajar yang Efektif Bagi Pendidik - Fariha Nadhira Lutfia; Adika Agil Firdaus; Hilma Fauziah; Mohammad Teguh; Sofyan Iskandar (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2025)
This article discusses the importance of educators' understanding of the nature and principles of learning in designing effective teaching strategies. In the ever-evolving world of education, mature educational management and learning planning are the keys to creating an optimal learning process. This study uses a literature review method by analyzing various relevant sources to explore the basic concepts of learning and the principles that support the effectiveness of the learning process. The results of the study indicate that understanding the nature of learning—as a process of interaction between students and the environment—and principles such as attention, motivation, activeness, direct experience, repetition, challenges, and individual differences, are very important for creating meaningful learning. Educators who understand these principles are able to create a learning environment that is conducive and responsive to the needs of students, while also answering the challenges of modern education. This article emphasizes that effective learning strategies must be understood in a deep understanding of the learning process itself.